The main directions of local self-government reform in Ukraine in the conditions of European integration - Shevchenko, Anatolii Yevheniiovych; Loshchykhin, Oleksandr Mykolaiovych; Kudin, Serhii Volodymyrovych; Shevchenko, Dmytro (Accent Graphics Communications & Publishing, 2020)
The monograph chapter identifies the main directions for implementing decentralization reforms in Ukraine and restructuring the system of local self-government. It substantiates the need for a comprehensive administrative-territorial reform aimed at ensuring the integrity of the state while preserving its unitary structure. The study analyzes the necessity of improving the legal regulation of the administrative-territorial system in line with Ukraine’s European integration commitments, particularly the Association Agreement with the European Union. It emphasizes the importance of clearly defining the powers of state authorities and local self-government bodies based on the principle of subsidiarity and ensuring a balance of interests within the public governance system. The chapter outlines directions for developing an effective regional policy of socio-economic and cultural development, establishing capable territorial communities, and expanding their powers in addressing local issues. It also highlights the need for budgetary reform and further legislative improvements in the field of decentralization and local self-government development.

У розділі монографії визначено основні напрями впровадження реформ децентралізації влади в Україні та реорганізації системи місцевого самоврядування. Обґрунтовано необхідність проведення комплексної адміністративно-територіальної реформи, спрямованої на забезпечення цілісності держави та збереження її унітарного устрою. Проаналізовано потребу в удосконаленні законодавчого регулювання адміністративно-територіального устрою з урахуванням євроінтеграційних зобов’язань України, зокрема положень Угоди про асоціацію з Європейським Союзом. Визначено важливість чіткого розмежування повноважень органів державної влади та місцевого самоврядування на засадах субсидіарності, а також забезпечення збалансованості інтересів у системі публічного управління. Окреслено напрями формування ефективної регіональної політики соціально-економічного та культурного розвитку, створення спроможних територіальних громад, розширення їх повноважень у вирішенні питань місцевого значення. Наголошено на необхідності проведення бюджетної реформи та подальшого вдосконалення законодавства щодо децентралізації влади і розвитку місцевого самоврядування.
Keywords: political reform; administrative reform; judicial reform; local self-government; the law of Ukraine; політична реформа; адміністративна реформа; судова реформа; місцеве самоврядування; закон України